Structure and evolution of the Fuegian Andes foreland thrust-fold belt, Tierra del Fuego, Argentina: Paleogeographic implications - Torres Carbonell, Pablo Juan (2008)
Field work in the frontal part of the foreland thrust-fold belt of the Fuegian Andes reveals complex relationships between stratigraphy and structure. Construction of balanced cross-sections allows us to infer the geometry and kinematics of structures controlling the thrust-fold belt evolution. The sequential restoration of these cross-sections to their undeformed state reveals the architecture of the Austral foreland basin in relation to the evolving deformation front. This front was developed after incorporation of the Paleocene-earliest Eocene foredeep of the basin to the thrust-fold belt. A wedge-top depozone formed over this former foredeep, bounded by the late-middle to late Eocene thrust front. The wedge-top basin was filled by a quartz-rich sandstone-dominated succession of Andean provenance. The same succession filled the foredeep formed northwards of the deformation front, active from late-middle Eocene. Further reactivation of compression led to backthrusting of the wedge-top clastic succession in the late Eocene, and to subsequent foreland propagation of the deformation, manifested by a sequence of low angle thrusts that affected the foredeep. The foredeep migrated forelandwards as the tectonic load advanced, to finally act as a passive depozone after the earliest Miocene, when the propagation of the deformation front stopped. The paleogeographic reconstruction from late Paleocene to earliest Miocene shows a strong linkage between tectonics and sedimentation in the Atlantic coast of the frontal Fuegian Andes.